2018
DOI: 10.4315/0362-028x.jfp-17-297
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation Protocols Influence the Thermal Resistance of Salmonella Enteritidis PT 30 in Fabricated Almond, Wheat, and Date Products

Abstract: Inoculation methods in pathogen inactivation studies ideally represent conditions that might occur in real-world scenarios. Surface contamination in or on low-moisture foods affects Salmonella thermal resistance, which is critically important for process validation applications. The objective of this study was to quantify the effect of inoculation protocol on the thermal resistance of Salmonella Enteritidis PT 30 in fabricated low-moisture foods. Almond meal, almond butter, wheat meal, wheat flour, and date pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…R 2 and greater SE values in general. Such variations have also previously been reported for Salmonella by Blessington et al (2013); Beuchat et al (2017), and Limcharoenchat et al (2018), who attributed the variations to inoculation method. In an extended study focusing on the effects of inoculation procedures on Salmonella thermal resistance in wheat flour, Hildebrandt et al (2016) reported that inoculation method impacted repeatability, population stability and inactivation kinetics of Salmonella in wheat flour, regardless of laboratory.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…R 2 and greater SE values in general. Such variations have also previously been reported for Salmonella by Blessington et al (2013); Beuchat et al (2017), and Limcharoenchat et al (2018), who attributed the variations to inoculation method. In an extended study focusing on the effects of inoculation procedures on Salmonella thermal resistance in wheat flour, Hildebrandt et al (2016) reported that inoculation method impacted repeatability, population stability and inactivation kinetics of Salmonella in wheat flour, regardless of laboratory.…”
Section: Discussionsupporting
confidence: 78%
“…In another study δ-value of 5.1 min for pre-fabrication inoculated flour and 4.7 min, for post-fabrication inoculated flour both at 80°C were reported, respectively, emphasizing the effect of inoculation protocol on Salmonella thermal death kinetics (Limcharoenchat et al, 2018). However, defining the inoculation protocol that is the closest simulation of real contamination routes based on product type and pathogen of concern remains a challenging subject for further discussion and future research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For comparing the influence of graininess and powder structures of food matrices on the heat resistance of E. faecium, an aliquot of 10 µL bacteria suspension was inoculated in~0.7 g wheat kernels and flour by gently hand mixing for 1 min and then dried for~40 min inside a biosafety hood until the a w of the sample equaled to that of a non-inoculated sample [12,15]. By simulating bacterial liquid distribution with the blue ink, the inoculation uniformity was determined by the color distribution with photos that the deviations of the L* and b* values were less than 8% and 7%, respectively, according to preliminary tests.…”
Section: Preparation and Inoculation Of Cell Suspensionmentioning
confidence: 99%
“…To investigate the effect of graininess and paste structures of materials on most heat-resistant bacteria, about 0.9 g wheat kernels and dough were inoculated by the same steps as described above. The drying time was determined by preliminary tests according to the a w of the sample using the water activity meter [2,12,15]. After equilibrating, the inoculated samples were transferred into TDT cells and closed immediately.…”
Section: Preparation and Inoculation Of Cell Suspensionmentioning
confidence: 99%